2010
DOI: 10.1159/000322259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute Renal Failure on the Relationship between N-Terminal pro-B-Type Natriuretic Peptide and Hemodynamic Parameters

Abstract: Background: We studied the influence of acute renal failure (ARF) on the relationship between N-terminal pro-B-type natriuretic peptide (NT-proBNP) and hemodynamic parameters. Methods: The echocardiographic parameters and NT-proBNP levels were compared between 26 mechanically ventilated patients with ARF requiring continuous hemodiafiltration and 44 control patients. Results: The relationships between NT-proBNP and left ventricular ejection fraction (p = 0.001), left ventricular end-diastolic volume (p = 0.03)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Many studies demonstrated that the impact of RI on NPs is independent from the cardiac function. It depends not only on the RI severity but also on the duration of disease [58]. …”
Section: Limitations Of Natriuretic Peptidesmentioning
confidence: 99%
“…Many studies demonstrated that the impact of RI on NPs is independent from the cardiac function. It depends not only on the RI severity but also on the duration of disease [58]. …”
Section: Limitations Of Natriuretic Peptidesmentioning
confidence: 99%
“…function being dependent not only on renal insufficiency severity but also on the duration of the disease [31]. Cruz et al calculated that in the presence of this associated condition, BNP levels increased of 1/3 compared to a patient with normal renal function [32].…”
Section: Authormentioning
confidence: 99%